Litter decomposition and nutrients dynamics in Nothofagus antarctica forests under silvopastoral use in Southern Patagonia - Bahamonde, Héctor Alejandro; Peri, Pablo Luis; Alvarez, Roberto; Barneix, Atilio José; Moretto, Alicia Susana; Martínez Pastur, Guillermo José (Agroforestry Systems)
The role of environmental variables on litter decomposition and its nutrient release in Nothofagus antarctica forest in Patagonia is poorly understood. Moreover, in these forests under silvopastoral use there are few antecedents. Litter decomposition and nutrient release of grasses and tree leaves were evaluated under different crown cover and two site quality stands during 480 days. Organic matter decomposition varied with crown cover for both types of litter, achieving mean values of 23 and 34% for maximal and minimal crown cover, respectively. Total transmitted radiation was the main environmental factor explaining 61 and 49% of the variation of grass and tree leaves decay rates, respectively. N, P, and Ca were mineralized during first 60 days in decomposing tree leaves and then immobilized without differences between crown cover. The K was immobilized during the evaluated period. In decomposing grass leaves the results varied according to site quality and time. There was a tendency of nutrient mineralization at the first 120 days and then immobilization. The removal of trees for silvopastoral use of N. antarctica may increase litter decomposition by changing the microclimate, but nutrients release or immobilization was mainly affected for their concentration in decomposing material. Fil: Bahamonde, Héctor Alejandro. Instituto Nacional de Tecnología Agropecuaria. Centro Regional Buenos Aires; Argentina. Universidad Nacional de la Patagonia Austral; Argentina Fil: Peri, Pablo Luis. Universidad Nacional de la Patagonia Austral; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina. Instituto Nacional de Tecnología Agropecuaria. Centro Regional Buenos Aires; Argentina Fil: Alvarez, Roberto. Universidad de Buenos Aires. Facultad de Agronomía; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina Fil: Barneix, Atilio José. Universidad de Buenos Aires. Facultad de Agronomía; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina ...